2021
DOI: 10.1111/jar.12950
|View full text |Cite
|
Sign up to set email alerts
|

‘The cure for us is a lot of things’: How young people with Prader‐Willi syndrome view themselves and future clinical trials

Abstract: Background: Despite work on the self-identities of people with intellectual disabilities, research has yet to describe the self-perceptions of people with Prader-Willi syndrome (PWS). The perspectives of those with PWS are also important for rapidly evolving clinical trials aimed at treating symptoms of PWS.Method: Twenty-one young people with PWS were administered a semi-structured interview that assessed how they perceive their syndrome and clinical trials. Transcribed interviews were reliably coded using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…First, we have found that individuals with PWS in our research programs have difficulty completing standardized questionnaires of their internal states (e.g., anxiety, depression), leading to unreliable data. Second, we have successfully used semi-structured interviews to explore the internal self-representations of young people with PWS ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we have found that individuals with PWS in our research programs have difficulty completing standardized questionnaires of their internal states (e.g., anxiety, depression), leading to unreliable data. Second, we have successfully used semi-structured interviews to explore the internal self-representations of young people with PWS ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, this proof-of-concept, mixed-method study justifies future work aimed at improving the social skills of people with PWS. Although challenged by their hyperphagia and food seeking ( 20 ), study participants learned social engagement, cognition, communication and motivation skills that furthered their friendships and reduced feelings of loneliness. Further studies are needed, yet findings bode well for the dissemination and implementation of the BOSS curriculum in the broader PWS community.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in early childhood, hyperphagia is attributed to aberrant neural feedback mechanisms involved in appetite regulation and satiety [9]. As a result, hyperphagic individuals with PWS view the world through a lens of hunger; they are constantly hungry, yet rarely feel full or sated [10]. Their unrelenting hunger leads to food seeking behaviors, including sneaking food and manipulating others to obtain food.…”
Section: Introductionmentioning
confidence: 99%
“…Such meticulous control of the food environment, such as locked food access and continuous supervision, amounts to the only ‘treatment’ or ‘management’ currently available for hyperphagia [ 9 ]. When describing their own aspirations, people with PWS typically identify control of the food environment as being fundamental to the type of care they wish to receive [ 10 ]. Families attempting to independently meet this considerable care demand typically experience significant levels of stress and greatly diminished quality of life [ 11 12 ].…”
Section: Introductionmentioning
confidence: 99%